HATE SPEECH IN JAPANESE AND INDONESIAN SOCIAL MEDIA: A CONTRASTIVE STUDY IN SOCIOLINGUISTIC AND CRITICAL DISCOURSE PERSPECTIVES - Amelya Septiana; Ruri Fadhillah Hakim; Mochammad Fredy (TELL - US JOURNAL, 2025)
This study aims to analyze hate speech on social media in the context of Japanese and Indonesian society using a sociolinguistic approach and critical discourse analysis. Data were collected from Twitter, Facebook, Instagram, and YouTube, totaling more than 2,000 data from both countries. The results show that hate speech in Indonesia tends to be explicit, emotional, and religiously or politically charged, while in Japan it is more implicit and implied in the form of metaphors or euphemisms. The analysis also reveals that hate speech does not only reflect individual opinions, but also reproduces dominant ideologies and maintains social inequality. This study is expected to be an important contribution to efforts to improve digital literacy and develop evidence-based policy strategies to address cross-cultural hate speech.